Johnson & Johnson's baby care products in China. - Chong, Yen Yin. (2008)
The report looks into the marketing environment of J&J's baby care market in China. An analysis was done on the marketing mix of J&J as well as those of its main competitors. Subsequently, a competitor analysis was also carried out and suitable recommendations were made for future improvements.